Dynamic Systems Modeling in Educational System Design & Policy - Jennifer Sterling Groff (Springer, 2013)
Over the last several hundred years, local and national educational systems have evolved from relatively simple systems to incredibly complex, interdependent, policy-laden structures, to which many question their value, effectiveness, and direction they are headed. System Dynamics is a field of analysis used to guide policy and system design in numerous fields including business and urban planning. Applying this tool to educational policy analysis offers insights into the hidden dynamics of the current system, and can be an invaluable tool in designing future scenarios. We explore underlying dynamics of the current US educational system using System Dynamics modeling, and offer an analysis of this tool and its practical application in the US educational system through a case study on the US state of Rhode Island in the 2007-2008 school year.